The use of passive voice in academic writing. Evidence from Danish, Norwegian and Swedish as L1 and L2 - Horbowicz, Paulina; Skrzypek, Dominika; Sobkowiak, Mikołaj; Kołaczek, Natalia (Folia Scandinavica Posnaniensia, 2020)
The paper studies the use of the passive voice in academic texts written in Mainland Scandinavian languages (Danish, Norwegian and Swedish) by their native speakers and by adult Polish learners of those languages. The corpus consists of 37 MA theses written in Scandinavia and in Poland. A number of referring verbs were chosen for the purpose of the analysis. The results show that while there are discrepancies in the use of the passive voice in texts written by Polish and Scandinavian students, they cannot be unequivocally diagnosed as resulting from the grammatical and stylistic influence of the mother tongue.